A new exoskeleton-type masterarm with force reflection based on the torque sensor beam - Yoon, Sang Kim; Lee, S.; Cho, C.; Kim, M.; Lee, C.-W. (Proceedings - IEEE International Conference on Robotics and Automation, 2001)
A new concept of the exoskeleton-type masterarm, composed of serial links, is introduced in this paper. To provide maximum range of human motion, several redundant joints are added to the serial links. In order to reduce the number of joints to be measured, kinematics of serial links was taken into consideration in design. Three measurable, controllable joints and three redundant free joints are used for the upper arm (shoulder), similarly to the forearm (wrist) while one measurable, controllable joint is used for the elbow. In particular, a torque sensor beam is designed for fine force reflection using the strain gauge. It detects the torque as well as its direction applied by the human operator, which allows the electric brake to be used as an actuator for force reflection. The electric brake constrains the joint movement so that the operator can feel the force. This electric brake outperforms the motor in terms of torque/weight ratio and makes the device light and compact. This masterarm measures the movement of the operator's arm precisely, and it can be used for teleoperation with a slave robot, or as a motion planner for an industrial robot.